Beyond Ohdo syndrome: A familial missense mutation broadens the MED12 spectrum. (4th September 2015) - Langley, Katherine G.; Brown, Jordan; Gerber, Richard J.; Fox, Janelle; Friez, Michael J.; Lyons, Michael; Schrier Vergano, Samantha A.
Abstract : Intellectual disability (ID) is estimated to affect 1–3% of the general population and is a common reason for referrals to pediatric and adult geneticists, as well as neurologists. There are many genetic and non‐genetic causes of ID; X‐linked forms are identifiable through their characteristic inheritance pattern. Current testing methods have been able to identify over 100 genes on the X chromosome responsible for X‐linked intellectual disability (XLID) syndromes. MED12 [MIM *300188] (mediator complex subunit 12) mutations have been linked to numerous XLID syndromes, including Lujan, FG, and Ohdo, and MED12 is included in many XLID panels. MED12 is located at Xq13.1 and its product has roles in transcriptional activation and repression. We describe two affected male siblings and their unaffected mother with a novel missense mutation in MED12, c.4147G>A (p.Ala1383Thr). The siblings share some features of Ohdo syndrome, including feeding difficulties, microcephaly, and speech delay. However, additional attributes such as hypertonia, eosinophilic esophagitis, penile chordee, and particular facial dysmorphisms depart sufficiently from individuals previously described such that they appear to represent a new and expanded phenotype. This case lends credence to the evolving theory that the subtypes of Ohdo, and perhaps other MED12 disorders, reflect a spectrum of characteristics, rather than distinct syndromes. As XLID panel testing and whole exome sequencing (WES) becomes a standard of care for affected males, further MED12 mutations will broaden the phenotype of these intriguing disorders and challenge clinicians to rethink the current diagnostic boundaries. © 2015 Wiley Periodicals, Inc.